2012
DOI: 10.1097/shk.0b013e318268c731
|View full text |Cite
|
Sign up to set email alerts
|

Role of Non-Muscle Myosin Light Chain Kinase in Neutrophil-Mediated Intestinal Barrier Dysfunction During Thermal Injury

Abstract: Neutrophils and non-muscle myosin light chain kinase (nmMLCK) have been implicated in intestinal microvascular leakage and mucosal hyperpermeability in inflammation and trauma. The aim of this study was to characterize the role of nmMLCK in neutrophil-dependent gut barrier dysfunction following thermal injury, a common form of trauma that typically induces inflammation in multiple organs. Histopathological examination of the small intestine in mice after a full-thickness burn revealed morphological evidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 31 publications
(71 reference statements)
0
8
0
Order By: Relevance
“…Our previous studies showed that in the early stages of severe burn injury, the phosphorylation level of the myosin light chain (mediated by the myosin light chain kinase) increased in intestinal mucosal epithelial cells, which played an important role in the occurrence of damage to the intestinal TJ barrier function and the increase in permeability in the early stages of burn injury (Chen et al, 2012). Subsequently, studies by some scholars using the membrane-permeable inhibitor of the myosin light chain kinase (PIK) and myosin light chain kinase gene knockout mice also came to similar conclusions (Guo et al, 2012; Zahs et al, 2012).…”
Section: Discussionmentioning
confidence: 83%
“…Our previous studies showed that in the early stages of severe burn injury, the phosphorylation level of the myosin light chain (mediated by the myosin light chain kinase) increased in intestinal mucosal epithelial cells, which played an important role in the occurrence of damage to the intestinal TJ barrier function and the increase in permeability in the early stages of burn injury (Chen et al, 2012). Subsequently, studies by some scholars using the membrane-permeable inhibitor of the myosin light chain kinase (PIK) and myosin light chain kinase gene knockout mice also came to similar conclusions (Guo et al, 2012; Zahs et al, 2012).…”
Section: Discussionmentioning
confidence: 83%
“…For example, uric acid,[33–35] high concentrations of glucose,[3639] mitochondrial dysfunction leading to increased reactive oxygen species,[22, 40] and increased lipids[17, 20] (burn patients suffer extensive lipolysis, despite hyperinsulinemia) are all scenarios that have both been observed in burn patients and are known activators of the inflammasome. It is also likely that many of our burned patients experience a “highly primed” inflammasome state,[41] as opportunistic infection (and hence bacterial-derived PAMPs, well-known inflammasome primers) is a common problem in burns. Current and future studies will focus on identifying the PAMPs and DAMPs associated with burn and inflammasome activation in our patients and animal models and whether genetic or pharmacological inhibition of inflammasomes improves post-burn outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The previous animal studies have revealed that MLCK chemical inhibitor ML-9 or peptide inhibitor PIK could significantly alleviate the barrier dysfunction, the changes of TJPs, the increase of MLC phosphorylation, and the hyperpermeability of intestinal epithelia in mice subjected to severe burns [94, 105]. Similarly, in MLCK knockout mice inflicted with 40% TBSA full-thickness burn, there was only slight elevation of intestinal permeability at 4 h after the injury, without obvious damage to the intestinal mucosa [106]. Therefore, after severe burn injury, MLCK upregulates the phosphorylation of MLC in intestinal epithelial cells, thereby leading to the barrier dysfunction and hyperpermeability.…”
Section: Reviewmentioning
confidence: 99%